Efektivitas Aplikasi Geogebra Terhadap Keterampilan Berpikir Krtitis Matematika Siswa - Nuril Huda; Al Ikhlas; Trisna Rukhmana; Nining Huriati (Departement of Mathematics Education, 2023)
Based on the results of observations on the online mathematics learning process in grade VIII A students of SMP Negeri 7 Kota Sungai Full with a total of 29 students, it is known that students do not understand the material provided by the teacher, this is due to learning mathematics One must think in order to be able to understand the mathematical concepts learned and be able to use these concepts correctly when he has to find answers to various mathematical problems, whereas the thought process cannot be obtained from learning remotely And also the network conditions in Sungai Full City are not good making students unable to study well, and not all students of SMP Negeri 7 Kota Sungai Full can use applications such as: Geogebra, Photomath, Cymath, and so on. This type of research is descriptive with a quantitative approach. The purpose of this study was to see the Effectiveness of Geogebra Applications on Students' Mathematical Critical Thinking Skills. The data analysis used in this study was by using the mean similarity test and t-test. Based on the results of data analysis using the t-test, a significance value (p-value) of < ∝ or in other words 0.000 < 0.05 means that H1 is accepted or in other words, students' mathematical critical thinking skills can be improved with the help of geogebra applications in mathematics learning.